Correlates of picky eating behaviour in children and its effect on growth - Shettiwar, Shweta; Wade, Minal (International Journal of Contemporary Pediatrics, 2019)
Background: Picky eating is common in preschool-aged children. Children’s picky eating behaviour has been linked both to being overweight and underweight. Authors objectives was to study the factors associates of picky eating behaviour on growth and nutritional status of children. Methods: A Cross-sectional study done in 200 parents of children between 1-5 year age visiting outpatient department. Picky eating behaviours were assessed using questions from children eating behaviour questionnaire. Results: In the study, the estimated prevalence rate was 25%, maximum 38% at 49 to 60 months. 26% of subjects with picky eating behaviour had height for age <-3SD (severely stunted) 38% of subjects with picky eating behaviour had weight for height <-3SD (severely wasted) as compared to only 4% in non-picky eating behaviour subjects. Low birth weight and exclusive breast feeding for less than 6 month, were found to be significant risk factor for development of picky eating behaviour, while no significant association was seen with the time of introduction of semisolid complimentary feeds. Conclusions: Picky eating is major parental concern and impacts growth of children. The children with picky eating behaviours need to be monitored for growth.